Neural stimulation and recording performance in human sensorimotor cortex over 1500 days. (13th August 2021) - Hughes, Christopher L; Flesher, Sharlene N; Weiss, Jeffrey M; Downey, John E; Boninger, Michael; Collinger, Jennifer L; Gaunt, Robert A
Abstract: Objective. Intracortical microstimulation (ICMS) in somatosensory cortex can restore sensation to people with spinal cord injury. However, the recording quality from implanted microelectrodes can degrade over time and limitations in stimulation longevity have been considered a potential barrier to the clinical use of ICMS. Our objective was to evaluate recording stability of intracortical electrodes implanted in the motor and somatosensory cortex of one person. The electrodes in motor cortex had platinum tips and were not stimulated, while the electrodes in somatosensory cortex had sputtered iridium oxide film (SIROF) tips and were stimulated. Additionally, we measured how well ICMS was able to evoke sensations over time. Approach . We implanted microelectrode arrays with SIROF tips in the somatosensory cortex (SIROF-sensory) of a human participant with a cervical spinal cord injury. We regularly stimulated these electrodes to evoke tactile sensations on the hand. Here, we quantify the stability of these electrodes in comparison to non-stimulated platinum electrodes implanted in the motor cortex (platinum-motor) over 1500 days with recorded signal quality and electrode impedances. Additionally, we quantify the stability of ICMS-evoked sensations using detection thresholds. Main results . We found that recording quality, as assessed by the number of electrodes with high-amplitude waveforms (>100 µ V peak-to-peak), peak-to-peak voltage, noise, and signal-to-noise ratio, decreased over time on SIROF-sensory and platinum-motor electrodes. However, SIROF-sensory electrodes were more likely to continue to record high-amplitude signals than platinum-motor electrodes. Interestingly, the detection thresholds for stimulus-evoked sensations decreased over time from a median of 31.5 μ A at day 100–10.4 μ A at day 1500, with the largest changes occurring between day 100 and 500. Significance . These results demonstrate that ICMS in human somatosensory cortex can be provided over long periods of time without deleterious effects on recording or stimulation capabilities. In fact, the sensitivity to stimulation improved over time.